Evaluation of Human Resource Preparedness and Internal Policies in the Management of Hazardous Chemical Waste - Herlina, Herlina (JURNAL KESMAS DAN GIZI (JKG), 2025)
Background: The management of hazardous chemical waste in healthcare facilities largely depends on human resource preparedness and the effectiveness of internal policies. Objective: This study aimed to evaluate the preparedness of human resources and internal policies in supporting hazardous chemical waste management at RS Grandmed Lubuk Pakam. Research Methods: This quantitative study with a cross-sectional design involved 44 respondents selected through stratified random sampling. Data were collected via structured questionnaires and document review, and analyzed using Spearman correlation and multiple logistic regression. Results: a total of 63.6% of respondents were categorized as prepared in hazardous waste management, and 56.8% perceived the hospital's internal policies as good. Bivariate analysis showed significant relationships between human resource preparedness (r=0.621; p=0.000) and internal policies (r=0.587; p=0.000) with waste management compliance. Multivariate analysis indicated that human resource preparedness (OR=6.65) and internal policies (OR=4.68) significantly affected compliance. Conclusion: Human resource preparedness and internal policies significantly influence compliance with hazardous chemical waste management; thus, continuous training, strengthened policy dissemination, and regular monitoring are recommended to enhance hospital waste management practices.